Joint decisions on household membership and human capital accumulation of youth : the role of expected earnings and local markets - Giannelli, Gianna Claudia [Verfasser]; Monfardini, Chiara [Verfasser] (My University, 2000)
"This paper analyses the effects of expected earnings and local markets conditions on the behaviour of young adults with high school diplomas. Decisions to either remain in the parental home or from a new household are modelled jointly with those of either gaining work experience or investing in a university education. A multinomial probit model estimates the probabilities of the different pairs of outcomes. Expected lifetime earnings oy youths are modelled and estimated, and serve as choice-specific regressors in the probit model. According to our results, the most important factor influencing the choice of studying and residing with parents os expected lifetime earnings from a university degree. A sizeable discouraged worker effect induces young people to study when labour market opportunities are poor. The cost of housing greatly influences the choice of working and living in the parental home. Two policy experiments offer some suggestions for policy makers. The first one measures the extent to which housing policies, targeted at reducing housing costs, would allow youths to live away from the parental home. A second indicates how much labour market policies, targeted at lowering youth unemployment to some desired levels, could decrease the number of discouraged workers that choose to study." (author's abstract, IAB-Doku) ((en))
Keywords: S 4.3.6 Human Capital; S 4 Kosten & Finanzierung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.4 Sozialer Wandel; G 2.4.2 Lebenskonzepte, -stile, Werte; I 2.2.1 Westeuropa; Jugendlicher; Humankapital; Junger Erwachsener; Einkommen; Arbeitsmarktchance; Bildungsinvestition; Bildungsertrag; Lebenssituation; Studienmotivation; Wohnsituation; Familie; Italien